Experimental economics: A survey - Chakravarty, Sujoy et al (2011)
Over the past few decades, experimental methods have given economists access to new sources of data and enlarged the set of economic propositions that can be validated. This field has grown exponentially in the past few decades, but is still relatively new to the average Indian academic. The objective of this survey is to familiarise the Indian audience with some aspects of experimental economics. The survey attempts to bring to the interested reader a flavour of this field. The survey is presented in five separate articles after this introduction. The notes and references for all articles are at the end of the survey. - Reproduced.
Keywords: Experimental methods